Ecomorfologia e variação morfológica intra-específica de Potamotrygon falkneri e Potamotrygon motoro (Chondrichthyes-Potamotrygonidae) na planície alagável do alto rio Paraná, Brasil. - Lonardoni, Alessandra Pasian (2009)
Potamotrygonidae comprises the only group of fish with cartilaginous skeletons that has adaptations to live exclusively in fresh water. The family is widely distributed in South American rivers that drain towards the Atlantic and has great richness, with about 19 to 21 valid species, distributed in three genera: Plesiotrygon, Paratrygon and Potamotrygon. The main features that distinguish this family from other elasmobranchs are the habitat, freshwater only, the presence of the pre-pelvic process, inability to retain urea, atrophy of the rectal gland and modification of Lorenzini's ampoules for operation in freshwater. In this thesis, the first chapter aimed to assess the ecomorphological diversification of Potamotrygon motoro and Potamotrygon falkneri in Paraná and Baia Rivers in relation to diet and habitat. There were significant differences between the two species diets and also on the diets of P. falkneri from the two sampled sites. There was significant correlation between the ecomorphological characteristics of both species and the use of habitat, at least in the Paraná River. The differential use of food resources for P. falkneri suggests that the ecomorphological differences detected allow functional performance of different morphological structures. Even considering the proximity of these rivers, it is possible to suggest that the intra-specific morphological variation in P. falkneri can occur by different ecological factors related to each environment, which seem to promote phenotypic divergence for individuals of this species.